Enhancing an instructional design model for virtual reality based learning - Chwen, Jen Chen; Chee, Siong Teh (ascilite, 2013)
In order to effectively utilize the capabilities of virtual reality (VR) in supporting the desired learning outcomes, careful consideration in the design of instruction for VR learning is crucial. In line with this concern, previous work proposed an instructional design model that prescribes instructional methods to guide the design of VR-based learning environments. This article provides a thorough elaboration on how formative research is employed to enhance the earlier model. The study has successfully generated five new hypothesized principles to enhance the robustness of the instructional design model through the formative research process. The newly derived hypothesized principles also provide insights into the design of various experimental studies for testing them in the effort to form a more comprehensive guide for the design of VR-based learning environments.